Rancang Bangun Vibration Test Bench untuk Mensimulasikan Kondisi Unbalance dengan Pengaturan Putaran dan Beban Unbalance - Maolana, Imam (P3M Politeknik Negeri Indramayu, 2017)
The goal of this work is to design and build a vibration test bench to simulate unbalance in rotating machine. The vibration test bench made of a 25 mm diameter steel shaft and length of 410 mm supported by two ball bearings. Two steel discs to variate unbalance load installed in the shaft powered by 0.5 Hp electric motor with maximum rotation of 1400 RPM. Inverter used to control rotation from electric motor. Vibration testing conducted at two condition; (1) without load and rotation variation, (2) unbalance load with variation of unbalance mass. Pick up point of vibration measurement at bearing house in radial and axial direction. The vibration parameter measured are amplitude and spectrum (wave form). Amplitude measurement using hand held vibrometer, while spectrum using accelerometer conected to a Data Acquisition. After testing the condition using unbalance load, we conclude that the vibration test bench match unbalance condition as described in theory which is high amplitude at machine frequency, and it’s value proportional to unbalance mass. We find that the highest amplitude is at horizontal direction where machine stiffnes is smallest. Vibration testing with no load condition show that there is harmonic in vibration spectrum indicating rotating looseness, probably caused by bearing wear.